Emotional numbing symptoms partially mediate the association between exposure to potentially morally injurious experiences and sexual anxiety for male service members. Issue 4 (8th August 2018) - Bhalla, Arjun; Allen, Elizabeth; Renshaw, Keith; Kenny, Jessica; Litz, Brett
ABSTRACT: Service members (SMs) returning from deployment are at risk of a range of sexual problems, some of which are thought to be related to psychological issues that may arise during deployment or combat. The current study sought to examine whether exposure to potentially morally injurious events (PMIEs) was associated with sexual anxiety (SA) above and beyond combat exposure and whether any such association was mediated by post-traumatic stress disorder (PTSD) symptom clusters. These questions were tested using data from self-report surveys collected from 221 partnered male Army (Active Duty, National Guard, or Reserve) SMs at three separate time points. Findings showed that exposure to PMIEs was significantly related to greater SA, with transgressions by self and perceived betrayal demonstrating unique associations when controlling for all factors of PMIEs. Moreover, total exposure to PMIEs was associated with SA above and beyond general combat exposure. PTSD symptoms partially mediated the association between exposure to PMIEs and SA, with emotional numbing accounting for significant unique indirect effects after controlling for other PTSD symptom clusters. The findings suggest that exposure to PMIEs is associated with SA, even when accounting for either combat exposure or PTSD symptoms, emphasizing the importance of this issue in understanding post-deployment problems in sexual intimacy.